MODEL KEPEMIMPINAN KONTIGENSI FIEDLER DALAM PENERAPAN E-GOVERNMENT - Fidentus Didakus Darma Saputra (STISIP Widyapuri Mandiri, 2024)
The utilisation of information and communication technology in government processes to improve the efficiency, effectiveness, transparency and accountability of governance. The application of E-government is important to help the government provide public services. The demand for transparency and accountability has finally become E-government as a key requirement so that the quality of good governance is not just a theory on paper. So that government agencies from the central to the regional level are obliged to implement the use of information systems and technology on a massive scale. The implementation of E-government in the regions is also in line with the demands of central government regulations that are concerned with the development of digital-based services. This research focuses on the role or model of government leadership. This research uses descriptive qualitative research methods. The results of the study found that the first Fiedler Contingency Model Leader Member Relationship is the most needed leadership model in the Public Service mechanism with data 60% strongly agree and 40% agree regarding this model which prioritises democracy as a pillar of service. The leadership model is carried out through democratic values. Second, the Degree Of Task Structure leadership model found that 80% strongly agree and 20% disagree. This means that the leadership model based on command lines is still relevant in the government bureaucracy. So that all duties and responsibilities are carried out based on TUPOKSI. So that there are no mistakes in providing policies or implementing policies. Third, namely Leader Position Power, the results showed that 40% strongly disagreed, 40% agreed and 20% strongly agreed. This means that this leadership model is less favoured by government officials because this model tends to be authoritarian and prioritise the selfishness of a leader.